Self-Efficacy and Its Relationship to Emotional Intelligence in a Sample of Widows - Mohammad Al Talahin, Fatima; Altarawneh, Rihan Thaher (Journal of Ecohumanism, 2024)
The aim of this study was to investigate the correlation of self-efficacy and emotional intelligence among widows in Amman, Jordan. The sample was comprised of 70 widows interviewed from local community associations and social support organizations. A quantitative, cross-sectional research design was used. Data were gathered with two standardized instruments, the General Self-Efficacy Scale (GSE; Schwarzer & Jerusalem, 1995) and the Schutte Self-Report Emotional Intelligence Test (SSEIT; Schutte et al., 1998). Descriptive statistics revealed that widows had a moderate level of self-efficacy (M = 29.35, SD = 4.56) and a moderately high level of emotional intelligence (M = 115.32, SD = 12.45). Frequency statistics revealed that 37.2% of the widows were within the moderate self-efficacy range, 34.4% were within the high range and 3.0% were only within the very low self-efficacy range. The internal consistency of both of the scales was high (self-efficacy scale a = .90, emotional intelligence scale a = .89). Inferential statistics showed that there was a positive correlation between self-efficacy and emotional intelligence (r = .46, p < .01). Furthermore, the results from the parametric analysis found that narrowly, education emerged as a significant differential factor on the score of self-efficacy (t = -.203, p = .047) with the widows who had a university level having a higher score than widows who had a secondary and below, while age and length of widowhood were not significant factors (p > .05). Hence, it was found that widows’ self-efficacy and emotional intelligence levels are in intermediate level in Amman and that the level of education is effective in the development of widows’ self-efficacy to cope with the life challenges.